Electronic and magnetic characterization of epitaxial VSe2 monolayers on superconducting NbSe2 - Kezilebieke, Shawulienu; Huda, Md Nurul; Dreher, Paul; Manninen, Ilkka; Zhou, Yifan; Sainio, Jani; Mansell, Rhodri; Ugeda, Miguel M.; van Dijken, Sebastiaan; Komsa, Hannu-Pekka; Liljeroth, Peter (Communications physics, 2020)
There has been enormous recent interest in heterostructures of two-dimensional van der Waals materials. Integrating materials with different quantum ground states in vertical heterostructures is predicted to lead to novel electronic properties that are not found in the constituent layers. Here, we present direct synthesis of a superconductor-magnet hybrid heterostructure by combining superconducting niobium diselenide (NbSe 2 ) with the monolayer vanadium diselenide (VSe 2 ). Molecular-beam epitaxy growth in ultra-high vacuum yields clean and atomically sharp interfaces. Combining different characterization techniques and density-functional theory calculations, we investigate the electronic and magnetic properties of VSe 2 on NbSe 2 . Low temperature scanning tunneling microscopy measurements show an absence of the typical charge density wave on VSe 2 and demonstrate a reduction of the superconducting gap of NbSe 2 on the VSe 2 layer. This suggests magnetization of the VSe 2 sheet, at least on the local scale. Our work demonstrates superconducting-magnetic hybrid materials with potential applications in future electronics devices. Whether two dimensional magnetic ordering exists in monolayers of VSe 2 has been the subject of recent debate. Here, the authors investigate monolayers of VSe 2 grown on an NbSe 2 substrate and demonstrate a reduction in the superconducting gap of the NbSe 2 and absence of charge density wave formation supporting the presence of a magnetic ground state in the VSe 2 .